Oxford Concise Dictionary of Mathematics - Christopher Clapham (Oxford University Press, 2009)
Authoritative and reliable, this A-Z provides jargon-free definitions for even the most technical mathematical terms. With 3,000 entries ranging from Achilles paradox to zero matrix, it covers all commonly encountered terms and concepts from pure and applied mathematics and statistics, for example, linear algebra, optimisation, nonlinear equations, and differential equations. In addition, there are entries on major mathematicians and on topics of more general interest, such as fractals, game theory, and chaos. Using graphs, diagrams, and charts to render definitions as comprehensible as possible, entries are clear and accessible and offer an ideal introduction to the subject. Useful appendices follow the A-Z dictionary and include lists of Nobel Prize winners and Fields' medallists, Greek letters, formulae, and - new to this edition - tables of inequalities, moments of inertia, Roman numerals, and more. This edition contains recommended web links at entry level, which are accessible and kept up to date via the Dictionary of Mathematics companion website.Fully revised and updated in line with curriculum and degree requirements this dictionary is indispensable for students and teachers of mathematics, and for anyone encountering mathematics in the workplace.